Updates on First-Line Treatment of Metastatic Pancreatic Adenocarcinoma - Strimpakos, Alexios S; Syrigos, Kostas N; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2011)
Despite the extensive research, mounting knowledge in the cancer field and enormous investments, pancreatic cancer remains a rather incurable disease with aggressive natural course and high mortality rate. The very slow progress is a result of the complex pathogenesis of this disease, which prevents us from targeting the culprit and making a step forward. Therefore, the field is still unexplored and this is a real challenge and opportunity for new ideas and novel approaches. In this paper, we will present the most interesting studies in the first line pancreatic cancer setting, presented at the American Society of Clinical Oncology (ASCO) 2011 Annual Meeting. While there are few studies testing the role of combining the cytotoxic S-1 and gemcitabine, the majority of the studies are examining the safety and impact of adding to the classic gemcitabine treatment novel molecular agents which target key pathways or overexpressed proteins. Image: The hedgehog pathway and the interaction of tumor cells with stromal cell.